Determination of Total Antioxidant Capacity of Rosehip (R. arvensis Huds) Growing in Turkey and Rosehip Species by Using CUPRAC Spectrophotometric Method - Karasakal, Ayca; Yalcin Gurkan, Yelda (Asian Journal of Chemistry, 2012)
L-Ascorbic acid (vitamin C) is the most important vitamin for human nutrition supplied by fruits and vegetables, and is the main water-soluble antioxidant in human plasma. L-Ascorbic acid is reversibly oxidized to form dehydroascorbic acid, which also exhibits biological activity. As a potent antioxidant, L-ascorbic acid scavenges reactive oxygen species including superoxide, protects isolated low density lipoprotein against oxidative modification and plays an important role in the regulation of intracellular redox status. The aim of this study was to measure antioxidant capacity of R. arvensis Huds and rosehip species, by using CUPRAC (the cupric ion reducing antioxidant capacity) spectrophotometric method.